2012
DOI: 10.3389/fnins.2012.00049
|View full text |Cite
|
Sign up to set email alerts
|

Digital Reconstructions of Neuronal Morphology: Three Decades of Research Trends

Abstract: The importance of neuronal morphology has been recognized from the early days of neuroscience. Elucidating the functional roles of axonal and dendritic arbors in synaptic integration, signal transmission, network connectivity, and circuit dynamics requires quantitative analyses of digital three-dimensional reconstructions. We extensively searched the scientific literature for all original reports describing reconstructions of neuronal morphology since the advent of this technique three decades ago. From almost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
75
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2
1

Relationship

5
5

Authors

Journals

citations
Cited by 120 publications
(77 citation statements)
references
References 51 publications
0
75
0
1
Order By: Relevance
“…Good curators cultivate three ‘p-virtues’: they are proactive, persistent, and patient in finding, requesting, and collating all data sets that investigators are willing to share. We regularly search the literature for any new publications describing neuronal morphology, promptly inviting the corresponding authors to deposit their digital reconstructions 17 . Our communications follow a systematic protocol with a set number of reminders.…”
Section: Recipes For Successful Data Sharingmentioning
confidence: 99%
“…Good curators cultivate three ‘p-virtues’: they are proactive, persistent, and patient in finding, requesting, and collating all data sets that investigators are willing to share. We regularly search the literature for any new publications describing neuronal morphology, promptly inviting the corresponding authors to deposit their digital reconstructions 17 . Our communications follow a systematic protocol with a set number of reminders.…”
Section: Recipes For Successful Data Sharingmentioning
confidence: 99%
“…Every month, NeuroMorpho.Org contacts authors of all papers with new morphologies identified by a literature survey to request that they share their data. The full list of papers with known morphologies and whether or not they are available in NeuroMorpho.Org is released on the repository's website [132]. …”
Section: Repositories and Standards: Code Data And Modelsmentioning
confidence: 99%
“…Here, we show that 3D reconstruction of the cerebral arterial vasculature can be achieved using existing methods originally developed for digital tracing and quantitative analysis of neuronal trees (Brown et al, 2005; Halavi et al, 2012; Scorcioni et al, 2008). Further, we demonstrate how the existing analysis methods can be used to study individual and population differences in cerebral vasculature at the level of the entire vasculature, specific arteries or single branches.…”
Section: Introductionmentioning
confidence: 99%